THE USE OF COMPOUND WORDS AND GRAMMATICAL COHESION IN THE ONLINE NEWS HEADLINE COLUMN OF THE JAKARTA POST - Nurise Nurise (Universitas Indraprasta PGRI, 2022)
The aim of this research is to find out The Use of Compound Words and Grammatical Cohesion in the Online News Headline Column of The Jakarta Post. The method used to analyze the headlines is descriptive qualitative method in the form of data from the online news headlines column in The Jakarta Post by examining each headline containing compound words and grammatical cohesion. The writer uses the Delahunty and Garvey’s theory to examine compound words and the theory of Halliday and Hasan to examine grammatical cohesion. After the writer analyzes the data in the online news headline column of “The Jakarta Post”, the writer can finally draw the conclusion. The results showed: 1) There are 3 types of compound words occurred in the online news headline column of The Jakarta Post, that is Compound Noun 80%, Compound Adjective 17%, and Compound Verb 3%. 2) There are 3 types of grammatical cohesion that occurred in the online news headlines column of The Jakarta Post, that is Reference 55%, Conjunction 44%, and Substitution 1%.